El posicionamiento ideológico como moderador en la relación entre la percepción de inseguridad y la confianza institucional (2026)
Insecurity is a current and persistent problem in Colombia, and being the second greatest concern of its citizens, it ends up affecting the perception of insecurity, trust in institutions and peace building. This study proposes 1) a first study that develops an exploratory factor analysis to identify the common factors of institutional trust and 2) a second study that seeks to establish whether right-wing authoritarian ideology and ideological positioning have a moderating effect on the relationship between perception of insecurity and institutional trust in the Colombian context. For this purpose, a cross-sectional study was carried out, with exploratory and correlational designs, respectively, with a sample of 1520 Colombian participants (50% women; mean age = 38.84) of the World Values Survey (WSV) with the variables of perception of insecurity, institutional trust, authoritarian beliefs and political ideological self-positioning. The results suggest, in addition to a categorization of institutional trust that is organized by international, political system, social and financial, and conventional institutions, it was found that the perception of security is a low predictor of trust in international organizations (R2 =.008 ;B=-.09; p=.002), and that the relationship with the 4 types of institutions is moderated by ideological positioning (B = .303 to .423). That is to say, that people aligned with a right-wing ideology trust more than left-wing or centrist people when they perceive that their context is insecure. Finally, it is recommended to continue exploring the role of political ambivalence in the study of crime and the erosion of interpersonal and institutional trust in the Latin American context using international databases for national and cross-sectional studies.